THE EFFECT OF CYBER ATTACKS ON CUSTOMER TRUST IN ISLAMIC BANKS AND CONVENTIONAL BANKS - Arlita Azzahra Addin; Lina Nugraha Rani; Valencia Kirana Rosadhillah; Binti Khusnul Hidayah (Universitas Airlangga, 2026)
Financial organizations are common targets of advanced cyberattacks and may be liable for substantial financial losses and reputational harm. Therefore, the objective of this study is to investigate the impact of consumer knowledge of cyber weapons, perceived threats, cybersecurity, and the adoption of PU for m-banking on consumer trust. Furthermore, in the wake of cybercrime, this study juxtaposes consumer trust in conventional and Islamic banks. Preliminary data were collected using quantitative methods through an online survey of conventional and Islamic bank customers (both users and non-users) in three selected provinces in Indonesia, characterized by a high density of banking activities, widespread use of mobile banking services, and high levels of exposure to cyber risks. The respondents had heard news about them being affected by details regarding cyber-attacks. A total of 200 respondents who fulfilled the criteria were included in this study. The method of analysis used was the Structural Equation Model-Partial Least Squares. According to the findings of this study, customers' knowledge of cyber threats hurt their trust in conventional and Islamic banks. However, perceived risk positively impacted customer trust in both types of banks. Cyber actions and the use of m-banking services both positively influenced customer trust in conventional and Islamic banks. Practically, these findings emphasized the importance of banks not only strengthening their cybersecurity strategies but also managing customer communication and the risks experienced to maintain and build trust in digital banking services after cyberattacks.